The Effectiveness Of Implementation Of Regulation Of The Mayor Of Surabaya Number 33 Of 2020 Article 16 Concerning New Normal Order Guidelines For Business Activities In Stores, Swalayan Stores, And Shopping Centers On The Condition Of The 2019 Corona Vir - Faisal Faisal; Suparno Suparno; Azis Budianto (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2021)
Since its appearance, Corona Virus Disease 2019 or Covid-19 has become a problem in various parts of the world. The sectors most affected by the Covid-19 pandemic are airlines, transportation, hotels, shopping centers and restaurants. This uncertain situation will further aggravate global financial stability. Mainly this has an impact on business activities in stores, convenience stores and shopping centers. Surabaya as a metropolitan city as well as the capital of East Java is participating in suppressing the prevention of Covid by making Perwali Surabaya No. 33 of 2020 concerning New Normal Procedures Guidelines for Business Activities in Stores, Supermarkets and Shopping Centers in pandemic conditions This research is a normative legal research and empirical law, namely research conducted by collecting legal materials, both primary, secondary and or tertiary.